An Analysis of Language Style Used in “The Princess Switch” Movie and Its Implications in Teaching Speaking - Lilian Salsabila; Pradnya Permanasari (Faculty of Humanities, Universitas Jenderal Soedirman, 2022)
This research aims to describe the types of language styles based on the level of formality theory by Joos in Sutherland (2016), identify the most frequent language used, and explain its implications in teaching speaking. The method used in this research was a descriptive qualitative method. The data was movie dialogues entitled